Integrated Sediment–Water–Biota Assessment of Petrochemical Contaminants, Partitioning and Ecological Risk in the Bonny Estuary, Niger Delta, Nigeria - Nkechi Blessing Chinedu; Ernest Nwanwunweneonye Orhuebor; Adedoyin Bankole; Gospel Effiong Isangadighi; Ubong Bernard Essien; Goodness Effiong Isangadighi; Jessica Gospel Isangadighi (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Petroleum-derived contaminants threaten tropical estuarine ecosystems through their persistence, bioavailability and toxicity, yet integrated multi-compartment evidence remains scarce for the Niger Delta. Objective: This study assessed petrochemical contaminants across the sediment–water–biota continuum of the Bonny Estuary, Rivers State, Nigeria, characterising their occurrence, sediment–water partitioning, bioaccumulation, ecotoxicological responses and ecological and human-health risks. Methods: Surface sediments, overlying waters and oysters (Crassostrea sp.) were sampled in the wet and dry seasons at eight stations spanning high-impact (B1–B3), mid-impact (B4–B6) and reference (R1–R2) zones, and analysed for 16 priority polycyclic aromatic hydrocarbons (PAHs), total petroleum hydrocarbons (TPH) and trace metals by GC–MS, GC–FID and ICP–MS, with biomarker, acute-toxicity and risk-index analysis (ANOVA, PCA and pollution indices). Results: A strong contamination gradient was observed: sediment ΣPAHs reached 7.18 mg kg⁻¹ and TPH 536 mg kg⁻¹ at B3 versus 0.54 and 62 mg kg⁻¹ at reference sites, with petroleum-tracer metals dominated by V (134), Cr (103) and Ni (74.6 mg kg⁻¹). Differences among stations were highly significant (ΣPAHs F=103.08, df=7,40, p<0.001, η²=0.947), and ΣPAHs correlated with organic carbon (r=0.90, p<0.001). Organic-carbon-normalised partition coefficients reached 185,118 L kg⁻¹ and oyster bioconcentration factors 1,686 L kg⁻¹, accompanied by elevated oxidative stress (MDA 8.6 nmol mg⁻¹) and genotoxicity (DNA tail moment 3.8); the Hakanson ecological risk index peaked at 209 and child seafood cancer risk approached 9.3×10⁻⁵. Conclusion: The Bonny Estuary exhibits pronounced petrochemical pollution, bioaccumulation and biological impairment, requiring NESREA-aligned monitoring, sediment-quality management and mangrove restoration.